2008
DOI: 10.1677/joe-08-0267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex steroids on plasma C-type natriuretic peptide forms: stimulation by oestradiol in lambs and adult sheep

Abstract: Although C-type natriuretic peptide (CNP) is crucial to postnatal endochondral growth, roles for the hormone in pubertal bone growth and the physiological effects of sex steroid substitution on CNP synthesis are not known. Using a plasma marker of CNP tissue synthesis (amino-terminal proCNP, NTproCNP), we have studied the effect of exogenous oestrogen (E 2 ) or testosterone (T) on plasma CNP forms and bone alkaline phosphatase (bALP) in pre-pubertal lambs.Responses to E 2 in non-cycling adult ewes were also st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The measurement of the serum BALP concentration was performed with a commercial immunoassay kit (Ostase ® , Beckman Coulter, Fullerton, CA, USA) using an automated biochemistry analyser (Access Immunoassay System ® , Beckman Instruments Inc.) based on chemical luminescence principles, assayed as previously described (Prickett et al, 2008). All samples were measured in duplicate and the mean values were calculated.…”
Section: Serum Biochemical Analysismentioning
confidence: 99%
“…The measurement of the serum BALP concentration was performed with a commercial immunoassay kit (Ostase ® , Beckman Coulter, Fullerton, CA, USA) using an automated biochemistry analyser (Access Immunoassay System ® , Beckman Instruments Inc.) based on chemical luminescence principles, assayed as previously described (Prickett et al, 2008). All samples were measured in duplicate and the mean values were calculated.…”
Section: Serum Biochemical Analysismentioning
confidence: 99%
“…The source of the elevated CNP, while not definitively identified, was thought likely to be derived from osteoblasts in bone tissue [70]. In marked contrast to the finding of a positive relationship between testosterone and CNP in pre-pubertal boys [65], Prickett et al observed no effect of testosterone administration on CNP in male lambs, a species difference in CNP regulation that the authors speculated could be related to the timing of testosterone intervention and the stage of pubertal maturation [70]. These studies point to the possibility that the influence of steroids on bone growth could be mediated, at least in part, through their regulation of CNP synthesis.…”
Section: Cnp Regulation In Other Tissues and Organsmentioning
confidence: 98%
“…Furthermore, uterine CNP and CNP transcription were observed to increase with the administration of exogenous estradiol to ovariectomized mice [1]. A steroid hormone-responsive consensus sequence has not yet been identified in the CNP promoter [70,89], suggesting that the observed effects of steroids on CNP expression could be secondary to their effects on the transcription of other proteins.…”
Section: Cnp Regulation In Other Tissues and Organsmentioning
confidence: 99%
See 2 more Smart Citations